DESIGN AND IMPLEMENTATION OF A SMART HYBRID SOLAR-WIND POWER SYSTEM WITH MPPT ALGORITHMS FOR IMPROVED ENERGY EFFICIENCY - Aftab Ahmed Soomro; Romaisa Shamshad Khan; Muhammad Danish; Basit Ahmad; Abdul Aziz; Asmatullah; Engr. Kashif Abbas; Muhammad Subhan Khan (Spectrum of Engineering Sciences, 2025)
The increasing demand for sustainable and efficient energy systems has led to the development of hybrid solar-wind power generation systems. This paper presents the design and implementation of a smart hybrid solar-wind power system optimized with Maximum Power Point Tracking (MPPT) algorithms for improved energy efficiency. The system integrates solar and wind energy sources with a battery storage system to address the intermittency of renewable energy and ensure stable power supply. A supervisory control system manages power flow, peak shaving, and energy storage, adapting to variations in supply and demand. To enhance system performance, a fuzzy logic-based control algorithm is introduced for intelligent power management. The hybrid system utilizes separate MPPT techniques for both solar panels and wind turbines, maximizing power extraction under changing environmental conditions. A novel hybrid MPPT algorithm adjusts to fluctuations in solar irradiance and wind speed, optimizing overall efficiency. Simulation results and performance analysis demonstrate a significant improvement in energy efficiency compared to standalone solar or wind systems. This study highlights the potential of integrating advanced MPPT control in hybrid renewable energy systems, providing a promising solution for sustainable and reliable power generation in remote and off-grid areas.